Polyaniline Modified Natural Zeolite as Adsorbent for Chromium(III) Metal Ion - Rina Nurianingsih; Sriatun Sriatun; Adi Darmawan (Jurnal Kimia Sains dan Aplikasi, 2019)
Zeolite is an inorganic material whose surface has a permanent negative charge in its crystal structure. This material consists of tetrahedral [SiO4]-4 and [AlO4]-5, which are connected by oxygen atoms in such a way as to form an open three-dimensional framework containing canals and cavities, as well as alkali or alkali metals for balancing the negative charge. This structure makes zeolites have the ability to adsorb. The ability of natural zeolite adsorption can improve by modifying the surface by adding polyaniline cationic compounds (PANI), which have an amine group (: NH2). Moreover, environmental pollution by metals is the biggest problem in daily life, one of which is the metal ion Cr(III), which is a waste from industrial processes. Therefore, it is necessary to have an effort to reduce waste. This study aims to determine the effect of the addition of polyaniline on the adsorption ability of natural zeolites to metal ions Cr(III). The research was carried out in several stages, namely activation of natural zeolite using HF 1%, modification with polymer from aniline monomers, and ammonium peroxidisulphate (APS), and testing the ability of adsorption on Cr(III) metal ions. The study on the ability to adsorb Cr(III) metal ions by PANI-modified zeolites was carried out on variations in the concentration of Cr(III) metal ions and the system pH. The results showed that natural zeolite successfully modified with PANI. The FTIR absorption band at wavenumber 1303 -1319 cm-1 and 1597 cm-1 indicated the presence of NH functional groups. Meanwhile, adsorption capability test data showed that the best adsorbent for adsorption of Cr(III) metal ions was zeolite-PANI 0.01M. The best pH was 4, the initial concentration of Cr(III) metal ions was 1000 ppm, and the percentage of absorption is 48.13%.